The Caribbean on the edge : the political stress of stability, equality, and diplomacy - Dookeran, Winston C. (University of Toronto Press ; United Nations, Economic Commission for Latin America and the Caribbean, 2022)
"In a time of persistent uncertainty, fragile eco-structures, the politics of "populism," and limits in institutional leadership, The Caribbean on the Edge acts as an analytical roadmap into a challenging era of globalization for the countries on the edge of history in the Caribbean, those often on a policy standstill pondering which way and how to turn. Winston Dookeran traces ideas evolved in development and diplomacy over the last decade to identify the path for new analytical leadership. The Caribbean on the Edge discusses the ideas central to leadership, including the political issues involved in development, governance, and diplomacy. Tracing the evolution of various schools of thought that influence policy choices, The Caribbean on the Edge introduces new approaches and risk factors that are aligned with the current realities in the region. Above all, this book is about the development of new practices that will usher in a radical shift in thinking, policy, and practice in order to unlock the paralysis of a Caribbean on the edge."--